Fabrication and Characterization of Chitosan-Polyvinyl Pyrolidone K-30 for Creatinine Transport Membranes - Retno Ariadi Lusiana; Riska Nurfida Annisa; Vinsencius Guntur Pandu Marcellino; Didik Setiyo Widodo; Hasan Muhtar (Jurnal Kimia Sains dan Aplikasi, 2023)
The investigation of membrane-based hemodialysis is an interesting study due to its efficacy in eliminating metabolic waste compounds, such as creatinine, from the body. However, not all membrane types exhibit optimal transport capabilities, necessitating modifications. In this study, we conducted modifications on chitosan (CS) membranes by incorporating polyvinyl pyrrolidone K-30 (PVP K-30) and assessing their physicochemical characteristics. The modified membrane underwent characterization and subsequent evaluation of its transport capabilities. The primary objective of this research is to design a membrane composed of chitosan and PVP K-30 with enhanced creatinine transport capabilities. The study commenced with the fabrication of CS membranes combined with CS-PVP, involving six variations of CS and PVP K-30 with volume ratios of 5:0, 4:1, 3:2, 1:1, 2:3, and 4:1. The resulting solution was then printed into a flat sheet membrane. All completed membranes underwent comprehensive characterization, including tests for functional groups using Fourier Transform Infrared (FTIR), membrane weight and thickness, porosity, water absorption, swelling, hydrophilicity, pH resistance, and biodegradation. In the final phase, the membrane was utilized in the creatinine transport process. FTIR analysis of the CS-PVP K-30 membrane revealed O-H and N-H group spectra at wave numbers 3363.06 cm-1 and 1587.17 cm-1, indicating hydrogen bonding between the two polymers. Characterization tests demonstrated that the CS-PVP membrane exhibited increased porosity, water absorption, swelling, and hydrophilicity. In the creatinine transport test, the CS-PVP membrane demonstrated enhanced creatinine transport ability compared to the CS membrane. The highest clearance value for creatinine was observed in the CS-PVP5 membrane, with an increase in the amount of PVP K-30 correlating with an elevated creatinine clearance value. The creatinine clearance values for the CS membrane, CS-PVP1, CS-PVP2, CS-PVP3, CS-PVP4, and CS-PVP5 were 0.30, 0.36, 0.37, 0.39, 0.42, and 0.46 mg/dL, respectively.